Ksfc - Real Promoter of Service Entrepreneurship - . Laxmisha, A.S (Ushus Journal of Business Management, 2021)
Development of entrepreneurship is cardinal and most crucial to the industrial development. It is the process of encouraging a prospective entrepreneur to set up an industrial unit whether production, processing or servicing. The development of entrepreneurship is dependant upon the policies, programmes and approaches of the Government. This task is carried out by the agencies like KSFC, TECSOK, Banks etc. Among them KSFC is a premier money lending institution functioning in the state of Karnataka. The subsidies given by it have helped to bring into existence numerous business activities. This paper is an attempt to see the type of entrepreneurship, i.e. industrial entrepreneurship of service entrepreneurship developed by the KSFC in Shimoga and Davangere districts of Karnataka State. The study based on both the secondary and primary data revealed that the Corporation is able to attract a large number of entrepreneurs in the service sector and assisting newer areas of activity. Careful selection and scanning of entrepreneurs, timely sanctions, need based lending policy, strengthening the entrepreneurial guidance, provision of working capital etc., are some of the suggestions offered by the paper. It has nourished many self made businessmen.